The Profiling of Design Product Using Bezier Curve for Customers Product Design Preferences - Yaakob, Mohd Yuhazri; Salahudin, Mohamad Tahkim; Sihombing, Haeryip; Wan Yaacob, Wan Nur Hidayah; Amir Mohamed, Kamarul; Sulaiman, Shamsudin (World Academy of Research in Science and Engineering, 2019)
This study is about the design properties of product based on the customer needs using Customer satisfaction, Kansei Engineering, Bezier Curve and Semantic Differential. To identify, investigate, and determine what are characteristics of products required by customer preferences compared to the image manipulated of product into Bezier curves. This study use 20 sedan cars (front view) that are manipulated into Bezier curve to find out which cars design are customers most preferred. From the data gathered, the most preferred Kansei words for sedan car are Luxury meanwhile for car preferences are BMW 5 Series, BMW F80 and Mercedes Benz E.